APPLICATION OF RESPONSE SURFACE METHODS TO DETERMINE CONDITION FOR POPULATION DOUBLING LEVEL PREDICTION - Rohim, Rabiatul Adawiyah Abdul; Yusop, Norhayati; Ahmad, Wan Muhamad Amir W (Journal of the sciences and arts, 2020)
The result shows that the predicted values were in good agreement with the experimental values in validation experiments, which confirmed the accuracy of the model. [...]this paper can offer the researchers with clear information about RSM methods. [...]the RSM was used to determine the optimum input variables that can appropriately reflect subjects' population doubling level. The value of the adjusted determination coefficient (Adj R2 = 0.9989) therefore confirmed that the model was highly significant, which indicated a good agreement between the experimental and predicted values of population doubling level. [...]the model is adequate for prediction in the range of experimental variables. According to Rai et al., (2016), adj R2 and prediction R2 should be within 20% to be in good agreement [9].